The use of corpus-based techniques in literary analysis : exploring learners’ perceptions - Abdul Wahid, Mohd Ridwan (International Islamic University Malaysia, 2011)
Although corpus linguistics is now known to broaden our understanding of various phenomena in linguistics and literature, little research has been undertaken to examine its effects on the learning experience of learners in the literature class. This study was aimed at exploring how learners respond to the adaptation of corpus-based techniques in their literary analysis. Specifically it tried to determine (1) how the participants perceived the use of corpus-based techniques in their literary analysis and (2) if these perceptions were influenced by their preference for literature or linguistics as a field of study. Participants for the study were 39 undergraduate English majors taking a language-based computer applications course at a public university in Malaysia. Data were collected from a specially designed questionnaire and group interviews. Findings indicated that more than 50% participants perceived all three techniques favourably in terms of learning enjoyment, improvement of understanding and wider applicability. The study also found that preference for literature or linguistics had no effect on their perceptions. To further appreciate their usefulness, the next step would be to apply these techniques in actual literature courses.